2018
DOI: 10.1089/neu.2017.5204
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor Cognitive Control Abnormalities in Australian Rules Football Players with a History of Concussion

Abstract: This study used oculomotor, cognitive, and multi-modal magnetic resonance imaging (MRI) measures to assess for neurological abnormalities in current asymptomatic amateur Australian rules footballers (i.e., Australia's most participated collision sport) with a history of sports-related concussion (SRC). Participants were 15 male amateur Australian rules football players with a history of SRC greater than 6 months previously, and 15 sex-, age-, and education-matched athlete control subjects that had no history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 46 publications
1
51
0
Order By: Relevance
“…It should also be noted that our MRI study was conducted on ex vivo brain samples, which somewhat limits the clinical relevance of the findings. However, both the scan time (i.e., 2 h) and the DWI sequences that were used are appropriate for future in vivo studies 23, 31, 57. As our current study only investigated rats given repeated mTBI, future in vivo studies could investigate the effects of a single mTBI using serial MRI at different postinjury times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that our MRI study was conducted on ex vivo brain samples, which somewhat limits the clinical relevance of the findings. However, both the scan time (i.e., 2 h) and the DWI sequences that were used are appropriate for future in vivo studies 23, 31, 57. As our current study only investigated rats given repeated mTBI, future in vivo studies could investigate the effects of a single mTBI using serial MRI at different postinjury times.…”
Section: Discussionmentioning
confidence: 99%
“…However, both the scan time (i.e., 2 h) and the DWI sequences that were used are appropriate for future in vivo studies. 23,31,57 As our current study only investigated rats given repeated mTBI, future in vivo studies could investigate the effects of a single mTBI using serial MRI at different postinjury times. Such investigations would provide important information related to diagnosis and recovery/cerebral vulnerability after a single mTBI.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, 15 the more‐challenging 1‐Back subtest provided superior classification of chronic mTBI relative to the 0‐Back subtest. Considering similar findings with other eye movement tasks, 28‐30 it appears likely that the additional working memory demands were instrumental in illuminating impairment related to chronic mTBI.…”
Section: Discussionmentioning
confidence: 65%
“…Impaired eye movements have been linked to axonal injury in postmortem tissue and on diffusion tensor imaging; 23‐25 abnormal functional connectivity in chronic mTBI extends to the visual system and its interactions with higher‐order cognitive processing 26 . Importantly, the types of eye movements that are most strongly impacted by mTBI are those that most heavily rely upon effective cognitive processing, as opposed to measures of basic neuromotor function 14,18,27‐29 . In particular, previous research conducted by our group 14,15 and others 28‐30 has shown enhanced sensitivity of eye movements to effects of mTBI under conditions of increased cognitive load.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation